Outcome of Endometrial Cancer Stage IIIA with Adnexa or Serosal Involvement Only - Jan J. Jobsen; Lambert Naudin ten Cate; Marnix L. M. Lybeert; Astrid Scholten; Elzbieta M. van der Steen-Banasik; Job van der Palen; Marika C. Stenfert Kroese; Annerie Slot; Eltjo M. J. Schutter; Sabine Siesling (Obstetrics and Gynecology International)
Objective. The aim of this study is to look at possible differences in outcome between serosa and adnexal involvement stage IIIA endometrial carcinoma. Methods. 67 patients with stage IIIA endometrial carcinoma were included, 46 with adnexal involvement and 21 with serosa. A central histopathological review was performed. Results. The 7-year locoregional failure rate was (LRFR) 2.2% for adnexal involvement and 16.0% for involvement of the serosa (P=.0522). The 7-year distant metastasis-free survival was 72.7% for adnexal involvement and 58.7% for serosa (P=.3994). The 7-year disease-specific survival (DSS) was 71.8% for patients with adnexal involvement and 75.4% for patients with serosa. Conclusion. Endometrial carcinoma stage IIIA with involvement of the adnexa or serosa showed to have a comparable disease-specific survival. Locoregional control was worse for serosa involvement compared to adnexa.